Typology of Small and Medium Enterprise Needs and Interventions - World Bank Group (World Bank, Washington, DC, 2020)
Due to their size and lack of scale, SMEs face many challenges to their growth, and governments on occasion choose to intervene to directly support firms. These interventions can be grouped into four broad areas - capabilities, markets, finance, and environment. This paper describes each type of intervention and the relevant needs and types of firms for each intervention.